Effect of seabuckthorn seed oil in reducing cardiovascular risk factors: A longitudinal controlled trial on hypertensive subjects. Issue 5 (October 2017) - Vashishtha, Vivek; Barhwal, Kalpana; Kumar, Ashish; Hota, Sunil Kumar; Chaurasia, Om Prakash; Kumar, Bhuvnesh
Summary: Background & aims: The present study aimed at investigating whether dietary supplementation of seabuckthorn seed oil which is rich in omega fatty acids at an oral dose of 0.75 ml could affect cardiovascular risk factors and reduce hypertension and systolic blood pressure. Methods: Toxicological evaluation and efficacy of seabuckthorn seed oil in reducing high fat diet induced dyslipidemia was initially conducted on adult male Sprague Dawley rats. 32 normal and 74 hypertensive and hypercholestrolemic human subjects participated in the randomized, controlled, double blind longitudinal study. Seabuckthorn seed oil or sunflower oil placebo was orally supplemented at a daily dose of 0.75 ml for 30 days. Results: Supplementation of seabuckthorn seed oil at a daily dose of 0.75 ml for 30 days resulted in normalization of blood pressure in hypertensive subjects. Dietary supplementation of seabuckthorn seed oil markedly reduces cholesterol, oxy-LDL and triglycerides in hypercholesterolemic subjects though it's effect on subjects with normal blood pressure and cholesterol is less pronounced. Seabuckthorn seed oil supplementation also improves circulatory antioxidant status in both normal and hypertensive subjects. Conclusion: The present study demonstrates the efficacy of seabuckthorn seed oil in reducing dyslipidemia, cardiovascular risk factors and hypertension in human population which may be due to presence of omega 3, 6 and 9 fatty acids in the oil. The improvement in antioxidant status can be attributed to presence of beta carotene and vitamin E in seabuckthorn seed oil. The trial was registered with Clinical Trial Registry of India (Clinical trial registration number – CTRI/2015/11/006368).